THE YEAR 1848 IN FRANCE. A FEW REMARKS AT THE 170TH ANNIVERSARY OF THE ADOPTION OF THE CONSTITUTION OF THE SECOND FRENCH REPUBLIC IN 1848. PART II - Konarski, Marcin (Review of European and Comparative Law, 2018)
The article is a continuation of the discussion undertaken on the occasion of the 170th anniversary of the Constitution of the Second French Republic. The author analyses the events that took place in France in the period between the shutdown of the national workshops in June 1848 and the adoption of the Constitution of the Second French Republic in November of the same year. A significant part of this article is the analysis of the provisions of the Constitution, with particular emphasis on the analysis of the institution of the President of the Republic, introduced for the first time to French constitutionalism.